NAMA DIRI ETNIK MELAYU PONTIANAK - NFN Irmayani (Balai Bahasa Kalimantan Barat, 2017)
Pontianak Malay community has tendency to use Arabic names as a marker of identity. The names are then abbreviated when they want to call the owner of the name. Interestingly, those abbreviated names are able to bring another variants. Therefore, this paper aims to describe Malay abbreviated proper names and those variants. This paper uses the proper names of Malay Pontianak as data. The data obtained from Malay community and also Facebook account Cinte Bahasa Melayu Kalbar (CBMK). In addition, the author also adds data to collect names carried by the society. Based on the data of collected proper names, it was found that the Pontianak Malay community abbreviated their name when they call the owner of the name. The abbreviated names are not only done by eliminating some of the elements of sound, but also by eliminating, replacing or adding to it. Additionally, the community also creates variant forms of the abbreviated names.